2013
DOI: 10.4317/jced.51176
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral Schwannomas: presentation of a series of 12 cases

Abstract: Introduction: Schwannomas are benign and not very frequent tumors of the peripheral nerves, derived from the nerve supporting Schwann cells. Study Design: Data were collected on the clinical manifestations (sex, age), location, size and symptonts of the lesions as well as the evolution time and the initial (presumption) diagnosis. Results: Twelve patients were documented, with a mean age of 29,5 ± 12,1 years (range 16-50) and a balanced gender distribution. The mean duration of the lesions was 42,17± 45,3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
(55 reference statements)
0
21
0
Order By: Relevance
“…Areas covered by masticatory mucosa have been described as the most frequently affected by PNSTs, and most neurofibromas and PENs are found in such locations ( 6 , 9 ). Schwannomas are found in several locations, but are frequent in the lips ( 6 , 19 ), GCTs in the tongue ( 6 , 12 , 18 , 20 ) and traumatic neuromas in the tongue and lips ( 6 , 10 , 12 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Areas covered by masticatory mucosa have been described as the most frequently affected by PNSTs, and most neurofibromas and PENs are found in such locations ( 6 , 9 ). Schwannomas are found in several locations, but are frequent in the lips ( 6 , 19 ), GCTs in the tongue ( 6 , 12 , 18 , 20 ) and traumatic neuromas in the tongue and lips ( 6 , 10 , 12 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sanchis et al ,9 in a series of 12 cases of intraoral schwannoma, reported the initial diagnosis to be correct in only two cases while the other cases were tentatively diagnosed as fibroma, dermoid cyst, adenoma and even residual cyst. Although the clinical picture of the lesion at the time of presentation in our case differed from that shown classically by schwannoma, the history given by the patient of the presence of a nodule-like mass initially and gingival overgrowth might have masked the true character of the lesion which was revealed histopathologically.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck is the most common site where SCH arise (30,31). In the oral cavity, however they are not as common as they represent 9.3% (30) – 13.5% (32) of all head and neck SCHs.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, it presents as a peripheral lesion, but rarely it may arise inside the jawbones (10,33). Its most common sites of manifestation are the lips and specifically the lower lip (10,11,31) or the buccal mucosa (5,34). Clinically, oral SCHs manifest as slow-growing solitary masses covered by normal appearing mucosa that measure a few millimeters to many centimeters in diameter (31).…”
Section: Discussionmentioning
confidence: 99%